High temperature during photorefractory stage attenuates photoperiodic responses during photostimulatory stage in male tree sparrows (Passer montanus) - Zothanmawii Renthlei; Montak Mongku; Subu Yatung; Ruth Lalpekhlui; Amit Kumar Trivedi (Theriogenology Wild)
Photoperiod is the most reliable environmental cue, though other environmental factors may affect breeding. We hypothesized that exposure to high temperatures at the photorefractory stage suppresses photoperiodic responses during the photostimulatory phase. Male adult photorefractory tree sparrows (n=10/group) were exposed to short photoperiod (SD;16 L:8D) but either high (30 ± 2 0C) or low temperature (20 ± 2 0C) for five or seven weeks and then long photoperiod (LD; 16 L:8D) for 30 days. mRNA levels of thyroid-stimulating hormone-β (Tshβ), type 2 deiodinase (Dio2), type 3 deiodinase (Dio3), gonadotropin-releasing hormone (GnRh), gonadotropin inhibitory hormone (GnIh), and EYA transcriptional coactivator and phosphatase 3 (Eya3) were measured in hypothalamic and expression levels of StAR, ER, CYP17, CYP11B, FOXOL1, and Nr4A1 were measured in the testes. Results show that exposure to 5 weeks of high temperature coupled with Short days suppresses expression of Tshβ, Dio2, and GnRh in the hypothalamus and StAR, ER, CYP17A1, and CYP11B in the testes under long days. No such effects were observed in birds exposed to high temperatures along with SD for seven weeks. These findings suggest that exposure to high temperature during the photorefractory stage modulates photoperiodic responses during the photostimulatory stage in time dependent manner.